Probabilistic linkage of national immunisation and state-based health records for a cohort of 1.9 million births to evaluate Australia’s childhood immunisation program - Gidding, Heather F; McIntyre, Peter B; Jorm, Louisa; Andrews, Ross M; Sheppeard, Vicky; Blyth, Christopher C; de Klerk, Nicholas; Liu, Bette; Snelling, Thomas; Fathima, Parveen; McCallum, Lisa; Moore, Hannah C (International Journal of Population Data Science, 2017)
Introduction Several countries have developed national immunisation registers, but only the Nordic countries have linked their registers to other health data in order to comprehensively evaluate the ‘real world’ effectiveness of vaccines. Nordic countries can link datasets deterministically using the national person identifier, but most countries, including Australia, don’t have such an identifier to enable this type of linkage. Objectives To describe the process for assembling a linked study cohort that will enable the conduct of population-based studies related to immunisation and immunisation policy. Methods National death and immunisation databases along with state health data (notifications of vaccine preventable diseases, perinatal data, hospital admissions and emergency department presentations) up until December 2013 were probabilistically linked (using demographic details) for children born between 1996 and 2012 in two states: Western Australia and New South Wales (42% of Australia’s population, combined). Results After exclusions there were 1.95 million children in the study cohort (live born children with both a birth and perinatal record which represents 97.5% of all live births in the state perinatal data collections - our source population) and 18.0 million person years of follow up (mean: 9.2 years per child). The characteristics of children in the cohort were generally similar to those only included in state perinatal databases and outcome measures were in keeping with expected figures from unlinked data sources. However, the lack of a dynamic national population register meant immigrants could not be included. Conclusions We have been able to develop a similarly comprehensive system to the Nordic countries based on probabilistic linkage methods. Our experience should provide encouragement to other countries with national immunisation registers looking to establish similar systems.